Toward Precision Psychiatry: A Scoping Review of Self-Monitoring and Artificial Intelligence for Bipolar Symptom Monitoring - Nursyafaat, Anastia; Sriati, Aat (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This scoping review aims to map and analyze the utilization of digital technologies, including self-monitoring applications, wearable devices, and hybrid interventions, for monitoring symptoms of bipolar disorder, as well as to explore their potential implementation in Indonesia. A systematic literature search was conducted across EBSCO Host, ScienceDirect, Oxford Academic, and Emerald Insight, focusing on studies published between 2020 and 2025 that addressed digital monitoring in individuals with bipolar disorder. The review identified ten studies that met the inclusion criteria, consisting of randomized controlled trials, mixed-methods studies, exploratory qualitative studies, pilot studies, and trial protocols. Key findings were categorized into four themes: (1) active self-monitoring via manual input or Ecological Momentary Assessment, which enhances self-awareness, promotes consistent daily routines, and supports symptom management; (2) passive monitoring and digital phenotyping using sensors and wearable devices, providing continuous objective data for early detection of relapse; (3) hybrid approaches integrating monitoring with therapeutic modules such as psychoeducation, mindfulness, and relapse prevention, which improve social functioning and treatment adherence; and (4) psychosocial factors and user engagement, highlighting the importance of personalization, peer support, inclusive language, and interactive features. Overall, digital interventions demonstrate considerable potential as a complement to conventional care by empowering patients, facilitating early detection of mood episodes, and enabling more personalized management. In Indonesia, the adoption of inclusive, evidence-based, and contextually adaptive digital strategies tailored to local digital literacy and infrastructure is expected to strengthen mental health services and sustainably enhance patient empowerment.